What keeps historical theme park visitors coming? Research based on expectation confirmation theory - Yuan, Li; Marzuki, Azizan (Frontiers in Psychology, 2024)
Culture is one of the most important factors in attracting tourists and influencing the tourist experience. In China, "theme park" is a new field of tourism research, an excellent theme park can not only drive the development of a city's tourism industry, but also help it better publicize its history and culture. The article takes Kaifeng, China as the background, and selects the Song Dynasty historical and cultural theme park, which was established based on the traditional ink painting Qingming Riverside Drawing, as an example, to study the factors affecting tourists' travel experience in historical and cultural theme parks, and based on which it explores the reasons for the formation of tourists' satisfaction and post-trip behavioral intentions, to provide references and suggestions for the development of cultural theme parks from the point of view of travel experience. Based on the expectation confirmation theory, this essay introduces five constructs, namely, expectation (tourism motivation), performance (service quality), confirmation (tourism experience), satisfaction, and post-trip behavior intention, to construct a model of the factors influencing tourists' satisfaction by tourism experience in historical theme parks and analyze the intrinsic correlation among the factors within the model. It is found that tourists' tourism experience is mainly affected by tourism motivation and service quality, satisfaction and post-trip behavior intention are jointly determined by the above three. According to the research results, this study believes that tourism motivation, service quality, and tourism experience should be the focus of attention of the current tourist destinations, therefore, focusing on tourists' motivation to optimize the quality of service, helping tourists to enhance the sense of tourism experience, and improving based on the above focuses is of great significance to promote the development of historical and cultural theme parks.Tourism is an industry of continuous innovation and development, which changes